2010
DOI: 10.1371/journal.pone.0011079
|View full text |Cite
|
Sign up to set email alerts
|

Host and Viral Genetic Correlates of Clinical Definitions of HIV-1 Disease Progression

Abstract: BackgroundVarious patterns of HIV-1 disease progression are described in clinical practice and in research. There is a need to assess the specificity of commonly used definitions of long term non-progressor (LTNP) elite controllers (LTNP-EC), viremic controllers (LTNP-VC), and viremic non controllers (LTNP-NC), as well as of chronic progressors (P) and rapid progressors (RP).Methodology and Principal FindingsWe re-evaluated the HIV-1 clinical definitions, summarized in Table 1, using the information provided b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 30 publications
(54 reference statements)
5
99
0
Order By: Relevance
“…Overall, our results support the findings of Lassen et al, (2009) and Casado et al, (2013) who found that entry efficiency of viruses from seven ES and three LTNP, respectively were lower than those from chronic progressors, suggesting that viruses with poor entry could lead to viral control. In support, one of our PSV clones, 398, a LTNP with longitudinal viral loads below 2000 copies/ml (Casado et al, 2010) had the lowest entry efficiency. More importantly, we show that the effect of Env entry efficiency on disease progression is not restricted to ES and LTNP.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Overall, our results support the findings of Lassen et al, (2009) and Casado et al, (2013) who found that entry efficiency of viruses from seven ES and three LTNP, respectively were lower than those from chronic progressors, suggesting that viruses with poor entry could lead to viral control. In support, one of our PSV clones, 398, a LTNP with longitudinal viral loads below 2000 copies/ml (Casado et al, 2010) had the lowest entry efficiency. More importantly, we show that the effect of Env entry efficiency on disease progression is not restricted to ES and LTNP.…”
Section: Resultssupporting
confidence: 55%
“…cavd.org). Analysis of longitudinal viral loads indicated that eight of the participants were progressors, and one was an LTNP based on classification by Casado et al, (2010). 2.2 PCR amplification and cloning of the env gene.…”
Section: Cohort Descriptionmentioning
confidence: 99%
“…Transcriptome analysis also included 9 elite/viremic controllers (ECs) and 5 chronic progressors, as previously defined (5). Patient characteristics are detailed in Supplemental Table 1 (supplemental material available online with this article; doi:10.1172/JCI45235DS1).…”
Section: Figurementioning
confidence: 99%
“…The other extreme of the spectrum of disease - rapid progression - has been the subject of much less research. Rapid progressors (RPs) can be defined by a number of criteria - generally including progressive immunosuppression soon after seroconversion and, in many cases, high levels of viremia (4,5). Limited data suggest that the concurrence of viral and host factors contributes to the severity of early disease (6).…”
Section: Introductionmentioning
confidence: 99%
“…The dramatic impact of the CCR5 ⌬32 mutation on disease pathogenesis (18,21,29,44) initially suggested that this mutation accounted for the ability of individuals to control infection, but this mutation is present in only a minor fraction of ES (11,25,35,40).…”
mentioning
confidence: 99%